PENGUJIAN MESIN TANAM PADI SISTIM JAJAR LEGOWO (JARWO TRANSPLANTER) DI LAHAN RAWA PASANG SURUT - Umar, Sudirman; Hidayat, A. R.; Pangaribuan, Sulha (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2017)
In Indonesia rice transplanting is the most widely used system by farmer in rice cultivation wich require 25-30% of total manpower. Optimizing mechanical  transplanting system is an alternative to overcome manpower shortage. The objective of this study is to evaluate the performance of jarwo transplanter in orther to improve its  efficiency. The experiment was conducted at Sidomulyo village, Kapuas regency, Central Kalimantan in dry season 2015 (April-September). Seedling to be used in this experiment was prepared using dapog method. Uniformity of planting, planting depth, the number of seedling embedded, and field capacity of the machine were oberved to determine the performance of jarwo transplanter. Results indicated that forward speed of 2.02 km/hour and planting width of 80 cm (4 rows), the effective field capacity was 6.28 hours/ha.Uniformity of planting achieved 98,08%  with an average number of seedlings was 3 to 4 seedling/hole and planting depth of 4.2 cm. There was 2.12 of holes without seedlings and 0.15% of floating seedlings. Application of Indo Jarwo Transplanter in the tidal swampland can overcome manpower shortages. Key word : transplanter, jarwo, tidal swampland, rice